MORPHOFUNCTIONAL STATE OF OF THE ORAL MUCOSA OF RATS UNDER THE INFLUENCE OF TOXICANTS IN THE OPTIMALITY CONDITIONS AND INSUFFICIENT INTAKE OF ALIMENTARY POLYPHENOLS - Glazunov Оleg Аnatol’evich; Glazunov Аnatoliy Оlegovich; Ozernova, Mayya Sergeevna (Journal of Education, Health and Sport, 2015)
The Aim of this research was to study assessment of morphofunctional state of the epithelium of the oral mucosa of rats under the action of fluorouracil in a vivarium full diet, as well as in experimental modeling the alimentary polyphenol deficiency Materials and methods. The study was conducted on 21 th white rat. Intact animals (7) were kept on a standard diet of the vivarium (DV). In group 2 (7) on the background of rats were treated orally with DV 5% solution of the pyrimidine uracil antimetabolite fluorouracil at a dose of 12.5 mg / kg body weight of rats (DV + fluorouracil). Rats of 3 group were kept on the diet without polyphenols (BPR). The experiment lasted 70 days. Results and conclusions Ftoruratsil in a vivarium diet had a depressing effect on the mitotic activity of epithelial cells. Changes of proliferation were partially offset by an increase in the number of dual-core cells. Fluorouracil in chronic alimentary polyphenol deficiency strengthened in the epithelium of inflammatory and destructive changes to the prevalence of destructive component. The thorny layer was a decrease in cell size and scope of their nuclei. Inflammatory changes in the lamina propria of connective tissue characterized by the increase of edema. Morphological disorders were more expressed in the group of rats treated with fluorouracil on background diet without polyphenols.